JENIS TUMBUHAN PAKAN DAN TEMPAT BERSARANG KUKANG (Nycticebus coucang) DI HUTAN LINDUNG PEGUNUNGAN MERRATUS, KALIMANTAN SELATAN - Hadi - Dahrudin; Wirdateti - - (ZOO INDONESIA, 2008)
Dahrudin, H & Wirdateti. 2008. Feed plants species and nesting trees of coucang(Nycticebus coucang) in Merratus protected forest, South Kalimantan. ZooIndonesia 17(1):7-14. A Survey on the feed plants species selection and nesting treesof coucang (Nycticebus coucang) in the Protected Forest of Merratus Mountains,South Kalimantan, was conducted for two weeks in April to May 2007. The surveyused exploration method and herbarium of the feedd plants were collected. From thestudy 54 plants were identified, four plants were used as their nesting trees, and 33plants were used as feed source.